Public Sector Employment in the 21st Century - Pittard, Marilyn (ANU Press, 2007)
This book addresses the transformations which have occurred in employment arrangements and practices in the Australian public sector over the past decade and the changes in responsibilities and accountability through employment contracts, whistleblower legislation and partnerships between government and the private sector. It provides a comparative context through studies of reconstruction of the public service in the United Kingdom and New Zealand. Themes of contractualisation, privatisation and outsourcing are explored and critically examined, as well as influences of the industrial relations legislative framework including the Work Choices legislation.